Profiling Flight Performance of Young Racing Pigeons (Columba Livia) in Training - F.T., Scullion; M.G., Scullion (Journal of Veterinary Healthcare, 2018)
Two groups of young pigeons were trained and flight parameters profiled over a flight path of approximately 90 km and a number of measures were developed to analyse their flight performances. An aerodynamic model of avian flight was fitted to the data to assess its value in predicting flight performances. Both groups, although trained and flown independent of each other, had very similar profiles through time. Race speeds home peaked between weeks 5 - 8 of training and averaged 15.0 (2.0) m/s for Group 1 and 15.6 (2.7) m/s for Group 2. Flight performance in early stages of training in this study seemed to be affected by previous health conditions but once training progressed beyond 5 weeks, young pigeons appeared to fly at a constant preferred speed.
Keywords: Aerodynamics; flight speed; preventative medicine; homing; avian navigation